La diáspora médica en Honduras: migración del personal salud (Revista Médica Hondureña, 2022)
Jhiamluka Zservando Solano Velásquez1 https://orcid.org/0000-0001-9987-483XAngie Torres Martínez2 https://orcid.org/0000-0003-3733-1367Roberto Galindo Donaire3 https://orcid.org/0000-0002-7000-4192